Data base: Pinus ponderosa seedlings - Nursery genetic trial [Conjunto de datos] - Aparicio, Alejandro Gabriel (Estación Experimental Agropecuaria Bariloche, Instituto Nacional de Tecnología Agropecuaria (INTA), 2024)
Supplementary dataset to the article "Mitochondrial DNA lineages and genetic variation of early growth traits in the Argentinean breeding population of Pinus ponderosa Douglas ex C. Lawson", New Forests : 1-21 (Published: 05 March 2024)